2023
DOI: 10.1002/path.6155
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in machine learning‐based assessment of tumor‐infiltrating lymphocytes in breast cancer: A report of the International Immuno‐Oncology Biomarker Working Group on Breast Cancer

Abstract: The clinical significance of the tumor‐immune interaction in breast cancer is now established, and tumor‐infiltrating lymphocytes (TILs) have emerged as predictive and prognostic biomarkers for patients with triple‐negative (estrogen receptor, progesterone receptor, and HER2‐negative) breast cancer and HER2‐positive breast cancer. How computational assessments of TILs might complement manual TIL assessment in trial and daily practices is currently debated. Recent efforts to use machine learning (ML) to automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…One common method used in machine learning-based assessment of TILs is image segmentation, where AI algorithms delineate regions of interest corresponding to TILs in tissue slides. By distinguishing TILs from other cell types and structures, machine learning models can quantify the percentage of TILs present in the tumor, as well as assess their spatial organization and relationship to other tumor features [49]. Artificial Intelligence-based mitosis scoring in breast cancer is a cutting-edge approach that utilizes advanced algorithms to automate the assessment of mitotic activity in tumor samples.…”
Section: Resultsmentioning
confidence: 99%
“…One common method used in machine learning-based assessment of TILs is image segmentation, where AI algorithms delineate regions of interest corresponding to TILs in tissue slides. By distinguishing TILs from other cell types and structures, machine learning models can quantify the percentage of TILs present in the tumor, as well as assess their spatial organization and relationship to other tumor features [49]. Artificial Intelligence-based mitosis scoring in breast cancer is a cutting-edge approach that utilizes advanced algorithms to automate the assessment of mitotic activity in tumor samples.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, these challenges are further complicated by technical factors, such as the lack of standardized parameters for data acquisition. [ 56 ]. AI-assisted TIL quantification remains a promising tool when handled by an experienced pathologist; however, forecasting clinical outcomes based on pre-treatment histopathologic images remains a challenging endeavor, hindered by the incomplete comprehension of the tumor immune microenvironment [ 52 , 56 , 57 ].…”
Section: Prognostic and Predictive Models On Digitalized Hande-staine...mentioning
confidence: 99%
“…Li et al's meta-analysis of 36 studies indicated that CA15-3 levels differ among breast cancer subtypes, suggesting its utility in differentiating TNBC from other forms [133]. Fu and Li emphasized the importance of combining CA15-3 with other tumor markers for more accurate clinical assessments [134], while Zhu et al highlighted its role in monitoring therapy outcomes and disease progression in metastatic breast cancer [135]. Additionally, Wang et al identified CA15-3 as a key biomarker in nipple discharge, aiding in diagnosis and prognosis [136], and Oliveira et al's development of a microfluidic device for CA15-3 detection underscores its practical application in clinical settings [137].…”
Section: Serological Biomarkers: the Importance Of Follow-upmentioning
confidence: 99%